Analisis Kebutuhan dan Perancangan UI Sistem Pendaftaran Medical Check-up Pasien Berbasis Mobile - Gultom, Eva; Tendean, Sandi; Darmianto, Amok (Universitas Multi Data Palembang, 2025)
Online medical check-up registration system is an innovation that can be applied by Health services to facilitate patients in registering. With the increasing demand for efficient and accessible health services, it is necessary to develop application that are functional and provide a satisfying experience for users. Therefore, this research was conducted with the aim of analyzing user needs and designing a user interface (UI) on an online medical check-up registration system. The methodology used in designing the interface design of patient online registration system is the Design thinking methodology. Design thinking is a methodology that can help in understanding user needs and developing solutions to problems that arise in an innovative way. This research produces a system design that can help develop digital health services, with the hope of facilitating access to health services and increasing the efficiency and effectiveness of the patient registration system.